2021
DOI: 10.1021/acs.analchem.1c00064
|View full text |Cite
|
Sign up to set email alerts
|

Specific Analysis of α-2,3-Sialylated N-Glycan Linkage Isomers by Microchip Capillary Electrophoresis–Mass Spectrometry

Abstract: Sialylated N-glycan isomers with α-2,3 and α-2,6 linkages play crucial and distinctive roles in diverse physiological and pathological processes. Changes of α-2,3-linked sialic acids in sialylated N-glycans are especially important in monitoring the initiation and progression of diseases. However, the specific analysis of α-2,3-sialylated N-glycan linkage isomers remains challenging due to their extremely low abundance and technical limitations in separation and detection. Herein, we designed an integrated str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…The reaction mixture was incubated at 37 °C for 2 h and added with 80 μL of ACN and 300 μL of 80% (v/v) ACN containing 0.1% (v/v) TFA to terminate the reaction. The solution was then purified by cotton-wool-based HILIC-SPE …”
Section: Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction mixture was incubated at 37 °C for 2 h and added with 80 μL of ACN and 300 μL of 80% (v/v) ACN containing 0.1% (v/v) TFA to terminate the reaction. The solution was then purified by cotton-wool-based HILIC-SPE …”
Section: Experimental Sectionmentioning
confidence: 99%
“…Meanwhile, the interface of MCE-MS avoids sample dilution in sheath flow interfaces which can results in low sensitivity, and solve the problems of the stability and reproducibility of spray in sheathless-flow interfaces. This MCE-MS technique has been applied into the glycosylation study. , To the best of our knowledge, there was no report about specific analysis of α-2,3- and α-2,6-linked sialylated N-glycan isomers using MCE-MS.…”
mentioning
confidence: 99%
“…Cheng et al. [73] designed a strategy that couples the linkage‐specific derivatization with a microchip CE‐MS for the specific analysis of α‐2,3‐sialylated glycans. The carboxyl groups of α‐2,6‐ and α‐2,3‐linked sialic acids were selectively derivatized with methylamine and N , N ‐dimethyl ethylenediamine (DMEN), respectively.…”
Section: Derivatization Of Glycansmentioning
confidence: 99%
“…Lageveen-Kammeijer et al [72] have reported a method that involves ethyl esterification of α-2,6-linked sialic acid and amidation of α-2,3 linkage in a simple two-step reaction. The one-pot reaction with a simple clean-up step allowed distinguishing and high-sensitivity characterization of sialic acid isomers from biofluids and tissues by CE-ESI-MS. Cheng et al [73] designed a strategy that couples the linkage-specific derivatization with a microchip CE-MS for the specific analysis of α-2,3-sialylated glycans. The carboxyl groups of α-2,6and α-2,3-linked sialic acids were selectively derivatized with methylamine and N,N-dimethyl ethylenediamine (DMEN), respectively.…”
Section: Derivatization Techniques Prompting Isomeric Identificationmentioning
confidence: 99%
“…Despite the importance of sialic acid epitopes in several health issues, accurate identification and quantification of sialylated glycans at the isomeric level remain a challenge due to the extremely heterogeneous sialyation and labile sialic acid residues ( Cheng et al, 2021 ). Today, selection/multiple response monitoring (SRM/MRM) coupled with liquid chromatography (LC) is emerging as an ideal technique for glycan quantitation ( Zhou et al, 2015 ; Seo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%